2013
DOI: 10.1007/s00268-013-2062-1
|View full text |Cite|
|
Sign up to set email alerts
|

Therapeutic Approach to Patients With a Lower‐Pitched Voice After Thyroidectomy

Abstract: The pitch-gliding ability and several specific stroboscopic findings were predictive of a response to direct voice therapy. Based on these findings, an individualized therapeutic approach could be applied, and the pitch of patients with a lower-pitched voice after thyroidectomy was restored earlier than expected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 31 publications
3
14
2
Order By: Relevance
“…Although deterioration in other acoustic parameters was also observed, the differences were not statistically significant. A previous study by the current authors found that patients who underwent thyroidectomy without laryngeal nerve injury also had lower-pitched voices 7 . However, the current study revealed greater decreases in fundamental frequency and speaking fundamental frequency after thyroidectomy with lateral neck dissection.…”
Section: Discussioncontrasting
confidence: 70%
“…Although deterioration in other acoustic parameters was also observed, the differences were not statistically significant. A previous study by the current authors found that patients who underwent thyroidectomy without laryngeal nerve injury also had lower-pitched voices 7 . However, the current study revealed greater decreases in fundamental frequency and speaking fundamental frequency after thyroidectomy with lateral neck dissection.…”
Section: Discussioncontrasting
confidence: 70%
“…High pitch tended to decrease in the transoral group, but statistical significance was not attained. Approximately 15% of patients exhibited clinically significant lower-pitched voices (ΔSFF > 12 Hz) one month after TOETVA, similar to the proportion exhibiting lower-pitched voices after open thyroidectomy (seen in this study and our previous reports) [ 12 , 13 ]. Our results suggest that TOETVA does not impose any additional pitch risk to those imposed by conventional open surgery.…”
Section: Discussionsupporting
confidence: 89%
“…Changes in all patients were calculated (postoperative change in SFF, ΔSFF = preoperative value of SFF – postoperative value of SFF, Hz). If the ΔSFF was > 12 Hz, the patient was considered to have a lower-pitched voice [ 12 , 13 , 21 ]. The software defines jitter values up to N < 1.1% and shimmer values up to N < 3.8% as normal.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with the results of previous studies [ 2 , 12 - 16 ], which proposed that pathological changes in thyroid patients’ voices primarily occur immediately after an operation and are characteristically temporary, with recovery over time. In particular, the fundamental frequency of the thyroidectomy patient’s voice clearly declines during the immediate postoperative period [ 12 , 17 ], and the cepstral analysis, which is based on the exact calculation of the fundamental frequency, adequately reflects this characteristic. This suggests that this decline in the fundamental frequency after the operation is due to the inability of the cricothyroid muscle, which affects the length adjustment of the vocal cords, to function properly with regard to muscle tension after surgery [ 18 ].…”
Section: Discussionmentioning
confidence: 99%